Money supply and economic growth of Nepal: ARDL approach - Kunwar, Keshar Bahadur (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
There are a number of theories illustrating the relationship between money supply and gross domestic product. Money supply can be defined as the total stock of money circulating in the economy. The circulating money involves the currency, printed notes, money in the deposit accounts, and in the form of other liquid assets. Valuation of money supply helps analysts and policy makers to frame the policy or to alter the existing policy of increasing or reducing the supply of money. The valuation is important as it ultimately affects the business cycle and thereby affecting the economy. This study sought to provide answers to the question, what are the effects of money supply on the gross domestic product in Nepal? The study undertook a causal research design using time series data from the period 1974/75 to 2017/18 to critically investigate the relationship between money supply and economic growth by establishing an empirical relationship that exists between them. The study employed the Augmented Diky fuller test and ARDL- VECM model. The results indicate the existence of a significant long-run relationship between money supply and economic growth as measured by GDP. LNBM is significant to LNGDP and LNGDP is also significant to LNBM so there is bi-directional causality. There is unidirectional relationship existing between LNINF to LNGDP and LNINF to LNBM. ECTcoefficient vale are negative and the p-value of above three approaches are also less than 5 percent which is desirable for the ARDL model.